SLANG LANGUAGE USED IN SING 2 MOVIE - Aini, Nur; Abdullah, Abdullah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to analyze the slang used in the film Sing 2. In addition, this study also aims to analyze the meaning and function of the use of slang. This research uses descriptive qualitative method. In this study, researchers used Chapman's theory (1988) to analyze the types of slang, Leech's theory (1981) to analyze the meaning of slang, and Allan & Burridge's theory (2006) to analyze the function of slang. The data source for this research was the film Sing 2. This research produced several findings. First, there are 2 types of slang used in the film Sing 2, namely primary slang and secondary slang. Second, there are 5 slang meanings in film sing 2, namely conceptual meaning, collocative meaning, connotative meaning, reflective meaning, and affective meaning. And finally, there are 7 functions of slang in this sing 2 film, namely to address, to humiliate, to initiate relaxed conversation, toform an atmosphere, to show intimacy, to reveal anger, and to express impressions